RETRACTED: Evaluation of psychometric characteristics of light triad personality questionnaire in nurses - Azam Farah Bijari; Leila Hefazi Torghabeh; Gholamreza Dehshiri (Brain and Behavior, 2022)
Abstract Introduction Personality is one of the important etiological factors of psychological factors. In this regard, one of the important factors in the success of people's social and psychological life is the light triad personality. They are a combination of sympathy, compassion, and humanity. On the basis of results of the research, it is not possible to trust the psychometrics characteristics of tools; it is necessary to evaluate the psychometric characteristics of these tools. Meanwhile, the aim of the present study is the evaluation of psychometrics characteristics of light triad personality in nurses. Methods The statistical population includes all nurses who were employed in the summer and autumn of 2020 in private centers and hospitals affiliated with Mashhad University of Medical Sciences. The sample of this study was 245 nurses who were selected by convenience sampling. To analyze the data, exploratory and confirmatory factor analysis, Pearson correlation, total question‐score correlation, and reliability analysis were used by using SPSSV22 and LISRELV8.80 software. Results The results of exploratory and confirmatory factor analysis confirmed the three‐factor structure of the light triad personality questionnaire. The findings of the convergent validity of the light triad personality questionnaire were evaluated and confirmed via its simultaneous implementation by the Social Health and Emotional Sympathy Questionnaires and its divergent reliability was confirmed by the Machiavellian Questionnaire. The reliability coefficient of the questionnaire was obtained for the factors of sympathy, compassion, philanthropy, and totality by using Cronbach's alpha coefficient, 0.83, 0.75, 0.70, and 0.92, respectively. Conclusion Finally, with regard to the desired validity and reliability coefficients, ease of implementation, scoring, interpretation, and explanation, as well as a short time to answer, it can be said that light triad personality questionnaires were qualified for use in psychological research to measure the rate of light triad personality.